The Mediterranean species of Malmgreniella Hartman, 1967 (Polychaeta: Polynoidae: Polynoinae), including the description of a new species - Barnich, Ruth; Fiege, Dieter (Journal of Natural History, 2001)
The present review is based on material from different localities in the Mediterranean Sea, and where appropriate, on type material; it comprises all Malmgreniella species known to occur in this area: i.e. Malmgreniella andreapolis (McIntosh, 1874), M. castanea (McIntosh, 1876), M. darbouxi Pettibone, 1993, M. lilianae Pettibone, 1993, M. ljungmani (Malmgren, 1867), M. lunulata (Delle Chiaje, 1830), M. polypapillata sp. nov. Two species are new for the Mediterranean: M. lilianae, previously only known from the southwest Atlantic, represents a new record, and M. polypapillata is a new species, occurring not only in the Mediterranean, but probably also in the northeast Atlantic. The seven Malmgreniella species listed above are described and figured, and an identification key is provided. Furthermore, the subfamily affiliation of the genus Malmgreniella Hartman, 1967 and the validity of Malmgrenia McIntosh, 1874 are discussed.
World Polychaeta Database (WPolyDb)